Neue Linke/Neue Musik: Kulturtheorien und künstlerische Avantgarde in den 1960er und 70er Jahren - Kutschke, Beate (Cologne Weimar Vienna Böhlau, 2007)
The cultural change that followed the events of 1968 is due less to concrete political interventions in state and society than to intellectual discourses spread through the mass media that popularized and politicized knowledge, especially scientific knowledge. The present study begins with this paradigm shift, which has recently received much attention in sociology and historiography. The fact that left-wing intellectual knowledge shaped a new way of life – gender and grassroots democracy as well as ecologically sustainable ways of life – is part of the familiar picture of the epoch. However, the fact that it was also culturalized in such remote areas as contemporary music and motivated numerous compositions and styles here is now being systematically examined for the first time using eight case studies. For 1968 research, avant-garde music proved to be an important cultural field for left-wing intellectual discourses and theories that are almost forgotten today.
Keywords: Avant-garde; Politics; Music philosophy and esthetics